'There’s a bit of banter': How male teenagers 'do boy' on social networking sites - John J. Whittle; Dave Elder-Vass; Karen Lumsden (2019)
This chapter discusses teenage boys’ use of banter on social networking sites such as Facebook by presenting data collected via semi-structured interviews and focus groups with boys and girls aged 11-16 from three schools in England. For male teenagers utilising social networking sites, banter is a common form of social interaction within peer groups and is a means of othering, and of performing and constructing hegemonic masculinity. Banter is characterised by the use of confrontational exchanges used to explore social boundaries and values amongst friends, and is strongly involved in male bonding rituals. It is employed as a means of negotiating status and of in-group inclusion and out-group rejection. We present findings which focus on: male teenagers learning to banter; the relationship between banter and bullying; and how banter overflows into other distinct but related practices.